Games to increase motivation towards physical activity in older adults/Juegos para elevar la motivación hacia la actividad física en adultos mayores - Milagros La Rosa Arias; Luis Alexander Zaldívar Castellanos; Odalis Martínez González; Yusleidy Marlie Gordo Gómez (Podium, 2021)
The decline in fertility and mortality rates has increased the percentage of people over 60 in Cuba. In this group, important changes are taking place in the psychosocial and biological spheres, where the practice of regular physical exercise is one of the main non-pharmacological strategies for ageing in a healthier way and improving the health-related quality of life of the elderly. However, there is an insufficient motivation on the part of the older adult towards physical activity, so it is proposed to apply a set of games that contribute to increase the motivation towards physical activity of them for which theoretical and empirical methods were used. The set of games is based on the methodological indications for the work with this population group and the methodological steps for the application of the games. The application of the statistical methods, verified that there are differences between the measurements made, after applying the set of games, which allows affirming the positive effect in the motivation towards physical activity in the elderly.